Educational assortative mating and household income inequality - Lasse Eika; Magne Mogstad; Basit Zafar (Federal Reserve Bank of New York, 2014)
We investigate the pattern of educational assortative mating, its evolution over time, and its impact on household income inequality. To these ends, we use rich data from the United States and Norway over the period 1980-2007. We find evidence of positive assortative mating at all levels of education in both countries. However, the time trends vary by the level of education: Among college graduates, assortative mating has been declining over time, whereas individuals with a low level of education are increasingly sorting into internally homogenous marriages. When looking within the group of college educated, we find strong but declining assortative mating by academic major. These findings motivate and guide a decomposition analysis, where we quantify the contribution of various factors to the distribution of household income. We find that educational assortative mating accounts for a non-negligible part of the cross-sectional inequality in household income. However, changes in assortative mating over time barely move the time trends in household income inequality. The reason is that the decline in assortative mating among the highly educated is offset by an increase in assortative mating among the less educated. By comparison, increases in the returns to education over time generate a considerable rise in household income inequality, but these price effects are partly mitigated by increases in college attendance and completion rates among women.
Keywords: D31; I24; J12; 330; assortative mating; education; inequality; household income; marriage